Coordination between midcingulate cortex and retrosplenial cortex in pain regulation - Qiu, Yunya; Lian, Yan-Na; Wu, Cheng; Liu, Li; Zhang, Chen; Li, Xiang-Yao (Frontiers in Molecular Neuroscience, 2024)
IntroductionThe cingulate cortex, with its subregions ACC, MCC, and RSC, is key in pain processing. However, the detailed interactions among these regions in modulating pain sensation have remained unclear.MethodsIn this study, chemogenetic tools were employed to selectively activate or inhibit neuronal activity in the MCC and RSC of rodents to elucidate their roles in pain regulation.Results: Our results showed that chemogenetic activation in both the RSC and MCC heightened pain sensitivity. Suppression of MCC activity disrupted the RSC’s regulation of both mechanical and thermal pain, while RSC inhibition specifically affected the MCC’s regulation of thermal pain.DiscussionThe findings indicate a complex interplay between the MCC and RSC, with the MCC potentially governing the RSC’s pain regulatory mechanisms. The RSC, in turn, is crucial for the MCC’s control over thermal sensation, revealing a collaborative mechanism in pain processing.ConclusionThis study provides evidence for the MCC and RSC’s collaborative roles in pain regulation, highlighting the importance of their interactions for thermal and mechanical pain sensitivity. Understanding these mechanisms could aid in developing targeted therapies for pain disorders.